2018
DOI: 10.1093/abm/kax030
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Personality Traits and 10-Year Course of Psychiatric and Medical Symptoms and Functional Impairment Following Trauma

Abstract: Background Personality is a major predictor of many mental and physical disorders, but its contributions to illness course are understudied. Purpose The current study aimed to explore whether personality is associated with a course of psychiatric and medical illness over 10 years following trauma. Methods World Trade Center (WTC) responders (N = 532) completed the personality inventory for DSM-5, which measures both broad domains and narrow facets. Responders' mental and physical health was assessed in the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 148 publications
6
17
0
Order By: Relevance
“…Anxiety and hostility are also established predictors of PTSD symptoms (DiGangi et al, 2013;Olatunji et al, 2010), and in the present study, we found significant moderate effects for both. ALP neuroticism predicted LRS, replicating a link between LRS and self-reported neuroticism observed in another sample of WTC responders (Waszczuk et al, 2018). Suicidality was predicted by depressivity and stress ALPs, which also replicates prior associations (Liu et al, 2006;R.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Anxiety and hostility are also established predictors of PTSD symptoms (DiGangi et al, 2013;Olatunji et al, 2010), and in the present study, we found significant moderate effects for both. ALP neuroticism predicted LRS, replicating a link between LRS and self-reported neuroticism observed in another sample of WTC responders (Waszczuk et al, 2018). Suicidality was predicted by depressivity and stress ALPs, which also replicates prior associations (Liu et al, 2006;R.…”
Section: Discussionsupporting
confidence: 75%
“…Despite 20 years passed since September 11 th , 2001, responders continue to show high rates of both psychiatric and medical sequelae of trauma (Bromet et al, 2016;Wisnivesky et al, 2011). Most participants in the present sample suffer from chronic symptoms and two years is not sufficient length of time to observe substantial change (Waszczuk et al, 2018). Hence, we did not seek to predict change, but thought it important to measure outcomes at a different time point from predictors to avoid transient methodological confounds (e.g., state effects, response biases) and allow for a clear temporal sequence between predictors and outcomes.…”
mentioning
confidence: 70%
“…One study found that a genetic polymorphism of the serotonin transporter (5-HTT (5-hydroxy tryptamine)] gene) may have led to higher rates of PTSD post 9/11 [45]. Personality characteristics associated with PTSD include negative affectivity, detachment and psychoticism, as well as less perceived self-efficacy [51,54]. In first responders, having only basic life-saving training versus more intermediate or advanced training, was found to be a risk factor for PTSD [31].…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…In regard to symptomatology and comorbidities, risk factors for more severe PTSD include having severe hyperarousal symptoms, experiencing bereavement, being injured by the attack, having a history of PTSD, depression or anxiety pre-attack, having other medical conditions diagnosed post-attack, higher levels of exposure to the attack and a lifetime trauma burden, especially post attack [27,42,60]. Finally, from a temperament perspective, using coping strategies such as substance use and avoidance, as well as callousness and perceptual dysregulation personality traits, can worsen the trajectory of the illness [51,60].…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…This research not only endorses the reliability and utility of dimensional assessments of personality disorders but increasingly indicates that maladaptive personality patterns may constitute an important transdiagnostic factor for general psychopathology. Research showed moderate to strong associations of maladaptive personality patterns with a range of other mental disorders, e.g., anxiety and depression ( 6 ), internalizing and externalizing disorders ( 7 ), psychotic disorders ( 8 ), substance-related disorders ( 9 ), and posttraumatic stress disorder ( 10 ). They have also been shown to be related to transdiagnostic variables, such as interpersonal problems ( 11 ), childhood maltreatment ( 12 ), maladaptive schemas ( 13 ), pathological beliefs ( 14 ), emotion dysregulation ( 15 ) or attachment anxiety and avoidance ( 16 ).…”
Section: Introductionmentioning
confidence: 99%